1992
DOI: 10.1002/art.1780350104
|View full text |Cite
|
Sign up to set email alerts
|

Variable‐Constant Segment Genotype of Immunoglobulin Kappa is Associated with Increased Risk for Rheumatoid Arthritis

Abstract: Objective. To further investigate the association of rheumatoid arthritis (RA) with a particular genotype identified by a restriction site polymorphism near the constant segment of immunoglobulin kappa (C,).Methods. The frequencies of genomic DNA polymorphisms detected within or near C, (the most C, -proximal variable segment [V,] B3 and a T lymphocyte marker [CDSA]) were determined by Southern blotting and hybridization. The frequencies of coding-region polymorphisms of C, (Km allotypes) were determined by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…MHC-related genes are also the major genetic loci controlling CIA susceptibility and severity in rats (16,17). Very little is known about the non-MHC genes in RA and other human autoimmune diseases (7)(8)(9)(42)(43)(44)(45)(46). It is suspected that many non-MHC genes are involved, each with a rclatively small effect on disease expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MHC-related genes are also the major genetic loci controlling CIA susceptibility and severity in rats (16,17). Very little is known about the non-MHC genes in RA and other human autoimmune diseases (7)(8)(9)(42)(43)(44)(45)(46). It is suspected that many non-MHC genes are involved, each with a rclatively small effect on disease expression.…”
Section: Discussionmentioning
confidence: 99%
“…A strong gcnetic contribution to susceptibility, most likely under non-Mendelian polygenic control, is evident from family studies (1). Although several biochemical pathways have been implicated in the pathogenesis of RA, very few susceptibility-and severity-controlling genes/ loci have been conclusively identified (2)(3)(4)(5)(6)(7)(8)(9). HLAaswciated genes are the most thoroughly documented and may account for as much ac 50% of the total genetic contribution to RA susceptibility (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is reported that there are at least 16 polymorphisms and 9 haplotypes in the Vk cluster of normal individuals (10). It has been reported that certain polymorphisms within the human Ig Vk locus are associated with rheumatoid arthritis (11,12). In addition, it has been shown that polymorphisms in the two human VH genes, both of which can encode anti-DNA Abs are related with the development of autoimmune diseases (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…A strong gcnetic contribution to susceptibility, most likely under non-Mendelian polygenic control, is evident from family studies (1). Although several biochemical pathways have been implicated in the pathogenesis of RA, very few susceptibility-and severity-controlling genes/ loci have been conclusively identified (2)(3)(4)(5)(6)(7)(8)(9). HLAaswciated genes are the most thoroughly documented and may account for as much ac 50% of the total genetic contribution to RA susceptibility (2).…”
mentioning
confidence: 99%